Efficacy of intravenous dexamethasone to reduce incidence of postoperative sore throat: A prospective randomized controlled trial - Dipanjan Bagchi; Mohan Chandra Mandal; Sabyasachi Das; Tirtha Sahoo; Sekhar Ranjan Basu; Sanhita Sarkar (Wolters Kluwer Medknow Publications, 2012)
Background: Sore throat and hoarseness are common complications of endotracheal intubation. It may be very distressing for the patient and may lead to sleep disturbances and unpleasant memories. Materials and Methods: This prospective double-blinded randomized control trial was aimed to determine the efficacy of prophylactic intravenous dexamethasone to reduce the incidence of postoperative sore throat at 1 hour after tracheal extubation. Ninety six patients of either sex aged between 18 to 60 years scheduled for elective surgeries needing general anesthesia with endotracheal intubation, were randomly allocated into two groups A and B. The patients received either intravenous 0.2 mg/kg dexamethasone (group A, n = 48) or normal saline (group B, n = 47) just before induction. Trachea was intubated with appropriate size disposable endotracheal tubes for securing the airway. Follow up for the incidence of sore throat, cough and hoarseness was done at 1, 6 and 24 hours post-extubation. Results: At 1 hour post-extubation, the incidence of sore throat in the control group was 48.9% compared with 18.8% in the dexamethasone group (P<0.002). Conclusions: Prophylactic intravenous dexamethasone in a dose of 0.2 mg/kg can reduce the incidence of postoperative sore throat at 1 hour post-extubation by around 30%, with the efficacy being around 60%.